Faktor-Faktor yang Mempengaruhi Seseorang Mengajukan Gugatan Cerai di Pengadilan Agama Cibinong Tahun 2021 - Julias Muda Prasetya; Suyudi Arif; Syarifah Gustiawati (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Building a home life is not always about harmony, there is often a problem whether it is small or great, internal or external factors, and one or both cannot carry out their duties as husband and wife. If both cannot control themselves in dealing with each problem, not eliminating the likelihood will only increase the larger one, so the final solution to resolve it is divorce. The purpose of this study is to find out what factors influenced a person to file a divorce at the cibinong religious court in 2021. The methods used are descriptive methods using a qualitative approach, the research used is field research (field research) to get the needed data. A divorce lawsuit taking place at the cibinong religious court in 2021 is affected by a continuing factor of contention and contention with a percentage of 69.04%, an economy with a percentage of 19.20%, abandoning one party with a percentage of 9.41%, apostasy and violence of a similar percentage of 0.77%, polygamy with a percentage of 0.33%, a moral/ moral crisis with a percentage of 0.30%, a husband is sentenced to prison by a percentage of 0.04%, a body defect of 0.04%, And forced mating with a percentage of 0.03%.Keyword: divorce, court, factors.